Analysis of Morphology Characters on Fuse Residuum of Knife Switch in Fire Ground. (2016) - Wang, Jing-jing
Abstract: In this paper, the integrated experimental system of material evidence for fire trace was used to make fuse residuum by simulating overload and short circuit of electric circuit, bad connection and fire. The scanning electron microscope can be utilized to observe and analyze the morphology characters on fuse fesiduum. The results indicate that in the condition of the overload and short circuit of electric circuit, bad connection and fire, the melted trace, s morphology is different, besides the amount of the oxide on the fuse residuum's surface is various. When the electric circuit is overload, there is no port in the fuse fesiduum. But there is some bled in the fuse fesiduum of the short circuit and fire. The dimple of fuse fesiduum is different.